MENGGUNAKAN PENDEKATAN NILAI INTRINSIK TERHADAP KEPUTUSAN JUAL ATAU BELI SAHAM PT. KIMIA FARMA - Kurniati Karim (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2015)
Objective is to determine the intrinsic value or stock price should be and to determine investment decisions to be taken when it is compared with the market price, if the stock price is at a position overvalued or undervalued, while the usefulness of writing that is as material for potential investors / investors in making investment decisions, and as reference materials and library materials for those who want to do research with the same object. The analysis showed that the intrinsic value in 2012 amounted to Rp 9.34 (that is intrinsic value (the actual value of the stock PT.Kimia FARMA, Tbk in 2012 amounted Rp9,34, this results in the can after calculating intrinsic value approach the present value. So if the stock price above the intrinsic value, the investor can sell, while conversely if it is below the intrinsic value then you should survive or bought from other investors. PT. Kimia share price interval FARMA, Tbk for 2012 is Rp209,38 s / d 275.36 per share with a 95% confidence level. It means that in 2008 the share price PT.Kimia FARMA, Tbk forecast to fluctuate from a low of Rp209,38 per share to the highest point of Rp 275.36 per share. Then linked to the first discussion above, so that the stock price above intrinsic value will reach a maximum at the highest price range is 275.36, and decreased to the lowest range of 209.38